EXPERIMENTAL DETERMINATION OF HEAT TRANSFER INTENSITY UNDER FORCED AIR CONVECTION IN INTERNAL CHANNELS OF FLAT PIPES - Zh. A. Mrochek; A. I. Diakov (Наука и техника)
The paper describes an installation and methods of experimental studies concerning heat transfer processes under forced air convection in internal channels of the flat pipes, which allow to take measurements of heat transfer intensity. The paper presents measurements of heat transfer intensity in respect of pipes with separate ribs of small height and pipes with channels, communicating with the help of round holes.